Some Biochemical Variables and its Relation to Muscular Fatigue in 800 m Freestyle Swimmers - Mohammed Elmaghraby, Ahmed; Rafat Aboseta, Mohammed; Nader Shalaby, Mohammed (International Journal of Psychosocial Rehabilitation, 2019)
The current research aims to identify the effects of 800 m freestyle swimming race on the concentration levels of lactic acid and other biochemical variables before and after performance. And variance rate and effect size of lactic acid on some biochemical variables before and after 800 m freestyle swimming race. The researchers used the descriptive approach. The researchers perpetually chose (14) 800 m freestyle swimmers representing their zone in all national championships and who were registered at the Egyptian Federation of Swimming (17-19 years). Results indicated that: - Concentrations of lactic acid and lactate dehydrogenase after 800 m freestyle swimming race increased by (87.28%) and (51.97%) respectively. - Concentrations of calcium and phosphor after 800 m freestyle swimming race increased by (8.80%) and (33.26%) respectively. - Effect size of lactic acid on some biochemical variables that induce fatigue in 800 m freestyle swimmers were between (0.149 – 0.729) before the race and (0.507 – 1.000) after the race. - The increase of some biochemical variables leads to increases in muscular acidosis that in turn decreases the physiological abilities of muscles and induces fatigue.